2004
DOI: 10.1111/j.1399-3038.2004.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of perennial allergic rhinitis with lactic acid bacteria

Abstract: Probiotics are perceived to exert beneficial effects in the prevention and treatment of allergic diseases via modifying the gut ecosystem. The aim of this study was to assess whether ingestion of fermented milk containing Lactobacillus paracasei-33 (LP-33), a strain newly isolated from the human intestinal tract, can improve the quality of life of patients with perennial allergic rhinitis. In a randomized, double-blind, placebo-controlled trial, we gave patients fermented milk with (n = 60) or without (n = 20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
139
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 21 publications
3
139
0
5
Order By: Relevance
“…9) Moreover, it has been proposed that DCs localized in the gut-associated lymphoid tissue can sample bacteria directly from the intestinal lumen and modify the immune homeostasis. 10) Clinical studies conducted in humans have indicated that LAB can alleviate the symptoms of atopy [11][12][13][14] and perennial allergic rhinitis [15][16][17] and enhance the anti-carcinogenic activity of the immune system. [18][19][20][21] Since the bacterial properties required for the different applications are clearly distinct, selection of the LAB strain is very important for a more rational use of these organisms.…”
mentioning
confidence: 99%
“…9) Moreover, it has been proposed that DCs localized in the gut-associated lymphoid tissue can sample bacteria directly from the intestinal lumen and modify the immune homeostasis. 10) Clinical studies conducted in humans have indicated that LAB can alleviate the symptoms of atopy [11][12][13][14] and perennial allergic rhinitis [15][16][17] and enhance the anti-carcinogenic activity of the immune system. [18][19][20][21] Since the bacterial properties required for the different applications are clearly distinct, selection of the LAB strain is very important for a more rational use of these organisms.…”
mentioning
confidence: 99%
“…Moreover, the immunomodulating effects of lactic acid bacteria have also been reported 2,3) and some specific strains of lactic acid bacteria are recognized to alleviate allergic diseases such as allergic rhinitis. [4][5][6] Although the etiology of allergic disease is still unclear, disturbance of the intestinal microflora, especially endogenous lactic acid bacteria, has been regarded as one of the important reasons related to allergic diseases. [7][8][9] Accordingly, improvement of the intestinal environment by the intake of probiotic lactic acid bacteria is considered effective for modulation of the immune system.…”
mentioning
confidence: 99%
“…rhinitis and asthma, and altogether included about 890 subjects. Lactobacillus paracasei-33, whether or not heat-inactivated, improved quality of life of patients with allergic rhinitis: both frequency and intensity of symptoms were significantly lower in the LP-33 group than the placebo group, after the 30-day treatment (Wang et al, 2004;Peng & Hsu, 2005). Likewise, Lactobacillus casei DN114 001 decreased the occurrence of rhinitis episodes and improved the health status of children with allergic rhinitis (Giovannini et al, 2007).…”
Section: Probiotics In the Treatment Of Rhinitis And Respiratory Allementioning
confidence: 99%